The Relationship Between The Nutritional Status of Toddlers and Family Economic Status During The Pandemic in The Village of Ciladeun Lebak- Banten - Putri Nazua Mas'ud; Rika Ferlianti (Junior Medical Journal, 2023)
The results of the Ministry of Health's Indonesian Nutrition Status Study (SSGI) survey recorded that 24.5% of babies under five years of age (toddlers) in Banten Province were stunted in 2021. Pandeglang Regency was recorded as the region with the highest prevalence of stunted toddlers in Banten, reaching 37.8% last year. Economic status in the family is essential in supporting children's growth and development. In addition, the nutritional status of toddlers is also very dependent on the parenting of parents or their environment on the quality of food, nutrients and physical health. This study aims to provide an overview of the nutritional status of toddlers from family economic status during the pandemic in Ciladeun village, Lebak-Banten. This research method is descriptive-analytic with a quantitative approach and research design using cross-sectional. Data collection techniques in this study used interviews and questionnaires. Data analysis used the SPSS Statistic version 24 and univariate and bivariate analysis. The results showed that the nutritional status of toddlers 2-5 years had a